Developing English for Nursing Materials Integrated With Task-Based Language Teaching (TBLT) and Soft-Skills - Dodi Mulyadi; Dian Candra Prasetyanti (Universitas Muhammadiyah Semarang, 2016)
Abstract. The ENP materials integrated with TBLT and soft-skills that suit the learners interests and needs contributed to facilitate students learning can prepare students for professional communication order to be ready in global competitive work. The research aimed to find out the existing ENP materials, to develop ENP Materials integrated with TBLT and soft-skills, and to know the effectiveness of implementing Developed ENP materials. The research employed R&D cycles including introductory phase, developing phase, testing and validating phase, and implementing phase. The data collecting techniques were validation sheet, test, observation and questionnaire. The results showed the developed ENP materials were valid, effective and practical. The validity was proved with validation mean of score were excellent and good category based on scoring rubrics. The effectiveness is proved by students learning achievement test with mean score 79. The practicality is proved with student responses 80% who enjoyed to use the ENP materials in learning.